Cable connecting assembly - WU JERRY (2013)
An electrical connector ( 100 ) includes an insulative housing ( 2 ) extending in a front-to-back direction, a first set of contacts ( 3 ) held in the insulative housing, and a second set of contacts ( 4 ) held in the insulative housing and including at least one pair of differential contacts ( 41 ) held in the insulative housing for transferring high-speed signals. Each first contact includes a nonelastic contact portion ( 36 ). Each of the second set of contacts includes an elastic contact portion ( 43 ) located behind the nonelastic contact portion along the front-to-rear direction. At least one set of first and second sets of contacts are permanently held in the insulative housing, while the other set of first and second sets of contacts is replaceably held in the insulative housing.